2012
DOI: 10.3892/ijmm.2012.1011
|View full text |Cite
|
Sign up to set email alerts
|

UV radiation-induced skin aging in hairless mice is effectively prevented by oral intake of sea buckthorn (Hippophae rhamnoides L.) fruit blend for 6 weeks through MMP suppression and increase of SOD activity

Abstract: Oxidative stress and oxidative photodamage induced by UV radiation can cause serious skin damage that is characterized by wrinkling, roughness, laxity and pigmentation. The effects of a sea buckthorn (Hippophae rhamnoides L.) fruit blend (SFB) containing sea buckthorn fruit extract, blueberry extract and collagen on UV-induced skin aging were examined by treating hairless mice for 6 weeks with UV irradiation and SFB administered orally. The effects of SFB were measured in the skin of these mice by phenotypical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 39 publications
(45 reference statements)
2
31
0
1
Order By: Relevance
“…Isorhamnetin inhibited hydrogen peroxide-induced apoptoic damage in H9c2 cardiomycotes by suppressing the production of reactive oxygen species and activating ERK and p53 [22], in addition to the inhibition of the overproduction of ox-LDL-induced reactive oxygen species in endothelial cell Eahy926 [23]. Sea buckthorn fruit feeding alleviated oxidative stressinduced skin damage in mice exposed to UV irradiation [24]. Sea buckthorn seed oil displayed hepatic protection in a carbon chloride induced mice model by improving their antioxidant defense system and suppressing lipid oxidation [25].…”
Section: Antioxidant Activitiesmentioning
confidence: 96%
See 1 more Smart Citation
“…Isorhamnetin inhibited hydrogen peroxide-induced apoptoic damage in H9c2 cardiomycotes by suppressing the production of reactive oxygen species and activating ERK and p53 [22], in addition to the inhibition of the overproduction of ox-LDL-induced reactive oxygen species in endothelial cell Eahy926 [23]. Sea buckthorn fruit feeding alleviated oxidative stressinduced skin damage in mice exposed to UV irradiation [24]. Sea buckthorn seed oil displayed hepatic protection in a carbon chloride induced mice model by improving their antioxidant defense system and suppressing lipid oxidation [25].…”
Section: Antioxidant Activitiesmentioning
confidence: 96%
“…A high antioxidant fruit blend containing sea buckthorn and blueberry fed to hairless mice suffering from UV irradiation resulted in a reduction of wrinkle formation and transdermal moisture loss. Sea buckthorn administration reduced the overly expressed matrix metalloproteinase (MMP) MMP-1 and MMP-9 induced by irradiation, and improved SOD avidity dramatically [24]. The dermal healing and anti-apoptotic effects of sea buckthorn fruit and oil for acute and chronic skin problems have been extensively investigated in various animal models with wounds, burns, and scalds [19,28].…”
Section: Skin and Mucosa Healthmentioning
confidence: 99%
“…Most commonly, it is added to anti-aging and anti-wrinkle cosmetics due to its firming and tonifying properties for aging skin [5]. Hwang et al (2012) suggested a sea buckthorn fruit blend against skin aging, because it functions by regulating moisture content, matrix metalloproteinase expression levels, and superoxide dismutase (SOD) activity [56]. SB oil alleviates dry, irritated, rough, flaking, and itchy skin [57].…”
Section: Sb Oil In Cosmeticsmentioning
confidence: 99%
“…UV exposure enhances ROS/RNS production [4,5,6], and the free radicals cause skin damage including apoptosis by interacting with DNAs, RNAs, and proteins [7]. Several lines of evidence have pointed to the implication of mitogen-activated protein kinase, aryl hydrocarbon receptor, transcription factors, such as nuclear factor-κB and nuclear factor erythroid 2-related factor 2, or matrix metalloproteinase in the degradation of dermal connective tissue following oxidative stress-induced skin damage [8,9,10,11,12,13,14,15]. …”
Section: Introductionmentioning
confidence: 99%